Cavitary lung lesion as sequelae of mild COVID-19 in a patient with HIV - Carl Tanba; Ruba Habib; Terina Chen; Nahar Saleh (Clinical Infection in Practice, 2023)
Cavitary lung lesions involve a large spectrum of acute to chronic infections, chronic systemic diseases, and malignancies. During the COVID-19 pandemic, we have seen an increase in lung cavitation, mainly secondary to bacterial infection however, there have been limited reports of these lesions with mild COVID-19 disease. There has been an association between severe COVID-19 infection and secondary bacterial/fungal infections and cavitary lung lesions. We report the first case of a 32-year-old man with well-controlled HIV who presented with cough and fever from what appeared to be a cavitary lesion as a sequela of his recent COVID-19 infection.